Realizing Regional Elections Based on People’s Sovereignty: Constitutionality of Regional Elections through the DPRD - Risman Setiawan (Yayasan Cahaya Generasi Positif, 2026)
Ambiguity in interpreting Article 18 of the UUD NRI 1945, particularly regarding the phrase “elected democratically,” has generated debate over direct regional head elections versus those held through the DPRD. This study aims to safeguard popular sovereignty within representative mechanisms while minimizing the adverse effects of high political costs and corruption risks. Employing a normative legal method, with legislative and conceptual approaches, the research addresses a gap in the literature on the constitutional design of regional head elections through the DPRD as an expression of popular sovereignty. The findings demonstrate that regional head elections conducted by the DPRD are constitutionally valid and consistent with democratic principles. This mechanism effectively reduces election expenditures and disrupts the cycle of political money. The study seeks to establish a normative basis for reinforcing popular sovereignty through an indirect election system that maintains popular legitimacy. In summary, the research concludes that regional elections conducted through the DPRD have significant implications for local government stability. The practical implications highlight the urgent need for regulatory frameworks to enhance public oversight and political party integrity, thereby ensuring popular sovereignty in the regional election process.